Pilar Munárriz Sánchez & Luis Leal Crespo, two Teachers in Exile from Girona to Caracas - Marqués i Sureda, Salomó (Historia y Memoria de la Educación, 2019)
This article offers part of the unknown memoirs written in Caracas by the teacher and inspector of primary education Pilar Munárriz, who had worked as inspector in the Spanish regions of Girona and Álaba. These memoirs were written the year her husband, Luis Leal Crespo, died. He worked as a teacher at the Teacher Education Schools of La Laguna, Oviedo and Girona. Afterwards, the couple left for the Dominican Republic where Leal continued to work in the field of Education. With the arrival of Trujillo’s dictatorship, they had to leave the country due to political pressures, and they finally settled in Caracas. In the Venezuelan capital Leal worked in different schools managed by his Republican colleagues and friends in exile. Finally, he created his own: the Leal School. These memoirs contribute to our knowledge of how family life was for a married couple of teachers in exile and it looks at the professional and political epiphanies that marked their lives, both in Santo Domingo and in Venezuela.